2018
DOI: 10.5433/1679-0359.2018v39n2p683
|View full text |Cite
|
Sign up to set email alerts
|

Effect of slow release urea in sheep feed on nitrogen balance

Abstract: The aim of this study was to evaluate the effect of inclusion of 0.0%, 0.4%, 0.8%, and 1.2% slow release urea (SRU) in sheep feed on nitrogen balance (intake, fecal and urinary excretion, nitrogen absorbed and retained and/or nitrogen balance). Four sheep with an average body weight (BW) of 30.8 ± 1.7 kg were distributed using a Latin square experimental design. Sheep were allocated in metabolic cages and received two meals a day. The data were subjected to analysis of variance and differences were tested usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Table (2) shows a significant increase (A<0.05) in the rate of lambs' consumption of feed significantly for the third and fourth treatment over the second. This finding agreed with those of [8][9][10]. In contrast [11] reported that the addition of 1.8 g/kg DM SRU improves DMI and digestion.…”
Section: Resultssupporting
confidence: 92%
“…Table (2) shows a significant increase (A<0.05) in the rate of lambs' consumption of feed significantly for the third and fourth treatment over the second. This finding agreed with those of [8][9][10]. In contrast [11] reported that the addition of 1.8 g/kg DM SRU improves DMI and digestion.…”
Section: Resultssupporting
confidence: 92%
“…In fact, serum urea concentration is proportional to the ammonia levels produced in the rumen (Karimizadeh et al, 2017). Most of the protein ingested is degraded by ruminal microorganisms, releasing ammonia, which is used for microbial protein synthesis (Geron et al, 2018). However, when large amounts of protein are fermented in combination with low availability of energy from carbohydrate degradation, a high rumen ammonia concentration is generated.…”
Section: Discussionmentioning
confidence: 99%
“…However, when large amounts of protein are fermented in combination with low availability of energy from carbohydrate degradation, a high rumen ammonia concentration is generated. The capacity of ammonia utilization by ruminal microorganisms is exceeded, so the excess is absorbed into the enterohepatic circulation, and in the liver is converted into urea, which, added to urea from amino acid metabolism, constitutes the major portion of plasma urea (Fernandes et al, 2012;Karimizadeh et al, 2017;Geron et al, 2018). However, it can be observed that the energy requirement for the lambs in this study was practically met (Table 3), with only a small deficit in its balance at 91-120 days, while the protein deficit was much higher (not being the protein requirement fully met).…”
Section: Discussionmentioning
confidence: 99%
“…These findings can be partially explained by an increased abundance and activity of fibrolytic bacteria in the rumen, such as Ruminococcaceae, which uses ammonia as its main nitrogen source due to both a higher level of NH 3 availability and better synchrony between nitrogen and carbohydrates in the rumen, when SRU is used as a partial substitution for SBM [ 38 , 39 ]. Furthermore, Geron et al (2016) found a better in vivo digestibility of crude protein in sheep fed with SRU as a partial replacement for SBM [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The partial replacement of SBM with SRU decreased the CFP of the treatment diet, expressed per 1 kilogram of diet (−10.98%; 449.91 vs. 505.41 g CO 2 -eq/kg diet) compared to the control diet due to the lower global warming potential (GWP) of SRU than SBM [ 24 ]. The highest GWP of soybean meal is mainly due to large transport distances and emissions related to land-use change (LUC), such as deforestation, which can lead to heavier emissions of greenhouse gases [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. These results agree with the findings of Salami et al (2021), who showed a 12% reduction in CFP (g CO 2 -eq/kg diet) when SBM and other plant-protein sources were replaced by SRU [ 8 ].…”
Section: Resultsmentioning
confidence: 99%